Legal Design for Informed Sharenting and Consent of the Child on Social Networking Sites - Özge Uzun Kazmacı; Esra Hamamcıoğlu; Ayşe Nilay Şenol; Argun Karamanlıoğlu; Güler Akduman Büyüktarakçı (Bratislava Law Review)
Children are increasingly active in social life through social networking sites and parents have begun sharing more posts including their children’s pictures and other personal data. As a result, children’s privacy becomes even more susceptible to the infringement of values within the bounds of right to privacy. The term “sharenting” refers to parents and other relatives sharing personal data of the child. Sharenting may cause significant risks that may affect the child all throughout their life such as “digital kidnapping” and potential future bullying among peers. When parents share posts on social networking sites, they essentially provide consent on behalf of the child. Valid consent from the parents and/or child is an important aspect in the infringement of personality rights. In all instances, the children's best interests should be taken into consideration. To raise awareness about protecting children and to ensure that consent is valid, legal design should be implemented in creating information texts. In this study, a system proposal has been developed for posting children’s photos on social media, which involves asking questions and displaying warning messages when children’s photos are shared. Within this framework, legal design is utilised in order to form clear and more comprehensible texts for users on social media platforms.